2023
DOI: 10.1038/s41598-023-37046-8
|View full text |Cite
|
Sign up to set email alerts
|

Tau protein binds to the P53 E3 ubiquitin ligase MDM2

Abstract: Tau gene mutations cause a progressive dementia and neurotoxic Tau forms deposited in neurofibrillary tangles are hallmarks of neurodegenerative tauopathies. Loss of non-canonical Tau functions may contribute to disease. In fact, Tau depletion affects the cellular response to DNA damage and tauopathies exhibit the accumulation of DNA lesions. Moreover, Tau modulates P53 activity and cell fate. Considering that MDM2 is the main antagonist of P53, we investigated, using orthogonal assays, if Tau interacts with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Since a loss of correlation with mutated P53 could indicate a role for Tau upstream of P53, and considering that MDM2 is the main E3 protein ubiquitin ligase and inhibitor of P53, the Tau-MDM2 link suggested a possible mechanism for the modulatory role of Tau on P53. Notably, we found that Tau binds and modulates MDM2 43 . Alternatively, considering that P53 activation of MDM2 transcription 44 is lost when P53 is mutated, this may explain the reduced MAPT - MDM2 correlation when P53 is mutated in LGG and GBM.…”
Section: Resultsmentioning
confidence: 78%
“…Since a loss of correlation with mutated P53 could indicate a role for Tau upstream of P53, and considering that MDM2 is the main E3 protein ubiquitin ligase and inhibitor of P53, the Tau-MDM2 link suggested a possible mechanism for the modulatory role of Tau on P53. Notably, we found that Tau binds and modulates MDM2 43 . Alternatively, considering that P53 activation of MDM2 transcription 44 is lost when P53 is mutated, this may explain the reduced MAPT - MDM2 correlation when P53 is mutated in LGG and GBM.…”
Section: Resultsmentioning
confidence: 78%
“…It has been shown that the P53 ubiquitin ligase MDM2 binds and regulates PRC2 stability ( Wienken et al, 2016 ) and that MDM2 modulates gene expression similar to PRC2 ( Wienken et al, 2017 ). Based on our recent work reporting the modulatory interaction between Tau and MDM2 ( Sola et al, 2023 ), we propose that Tau modulates PRC2 stability through a MDM2-dependent mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…This may be explained by the intrinsically disordered nature of Praja1, lacking a specific tertiary structure. E3 ligases containing disordered regions adopt suitable conformations in a partner-dependent manner [29,30]. In addition to the characteristics of Praja1, the biochemical properties of interacting proteins may also facilitate the recognition by Praja1.…”
Section: Discussionmentioning
confidence: 99%